Dental Management of a Patient with Amelogenesis Skeletal Class III Multidisciplinary Malocclusion & Anterior Open bite; A Case Report - Tehranchi, Azita; Behnia, Hossein; Seyedan, Kaveh; Rezvan, Ramyar; Tehrani, Zahra (Journal of Dental School, 2018)
Objectives Amelogenesis imperfecta (AI) comprises a clinically and genetically heterogeneous group of conditions that affects the dental enamel, occasionally in conjunction with other dental, oral, and extra oral tissues. The purpose of this case report was to describe the necessity of the multidisciplinary approaches taken to treat a young patient diagnosed with hypocalcified-type of amelogenesis imperfecta along with skeletal class III jaws relationship and anterior open bite. Case A 19 year-old female was presented to the department of orthodontics, School of Dentistry at Shahid Beheshti University of Medical Sciences (Tehran, IRAN) with the chief complaints of dental sensitivity to hot and cold, teeth discoloration leading to esthetic concerns. On examination the patient was confirmed as skeletal CL III with a long face syndrome and severe anterior open bite. The patient reported difficulty with mastication and poor self-image due to teeth appearance .Interdisciplinary team approach was proposed in a three phase treatment plan: pre-surgical treatment, surgical treatment, postsurgical treatment. This approach enabled the team to successfully improve the patient’s facial profile, resolve malocclusion, and normalize the aesthetic. Conclusion This case management revealed the importance of having a coordinated team approach consist of orthodontist, oral surgeon, and prosthodontist as a necessary key to a successful treatment. This approach is essential for successful management of structural, aesthetic, and functional issues as well as an achievement of high patient’s satisfaction.